PENGARUH JOB ENRICHMENT TERHADAP KEPUASAN KERJA, MOTIVASI DAN KOMITMENT ORGANISASI PT FAJAR SURYA WISESA - Fransisca Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Human resources is the most important function in a company, because its quality determines the company's success rating. Employee's satisfaction, motivation, and commitment are the keys to the company's efficiency and effectivity, which are also related to the company's job enrichment that creates job control and responsibility. Data used in this research is premier data obtained by sending out questionnaires to 65 employees of PT Fajar Surya Wisesa. We are using the simple linear regression Analysis tool, which includes correlation coefficient, coefficient of determination, regression of significance, and MANOVA testing. The result of this research shows that job enrichment significantly determines job satisfaction, motivation, and commitment.Keywords : job enrichment, satisfaction,motivation,commitment